MEASURES FOR ORGANIZING LIBRARY AFFAIRS IN THE TURKESTAN ASSR - Olimjonov X. A. (TARIXIY TADQIQOTLAR, 2025)
The article examines the process of library nationalization in the Turkestan region, initiated on April 14, 1919. By decree of the Turkestan Council of People's Commissars, all libraries were transferred under the jurisdiction of the People's Commissariat of Education, where a special library department was established. The functions of the Turkestan People's Library, librarian training, catalog system development, and bibliographic activities are analyzed. The library’s role as a cultural and educational center, its organization of reader conferences, and publishing activities are highlighted. Special attention is given to the expansion of library collections, technical modernization, and the promotion of national literature.